Numerical Study on Aerodynamic and Aeroacoustic Performances of Bioinspired Wings - Dichen Li; Chuang Wei (Applied Bionics and Biomechanics)
Noise control has become one of the key issues to be considered in modern aeronautical machinery design. Many efforts have been devoted to noise reduction of airfoils and wings, including traditional flow control methods. In fact, some animals in wild nature exhibit superior aerodynamic and aeroacoustic performance, providing novel ideas for solving this engineering problem. In this research, bionic technology is used to obtain quiet and efficient wing. Inspired by the owl’s wing, we propose two bionic configurations, one coupled with leading edge waves and trailing edge serrations. The Large Eddy Simulation and the Ffowcs-Williams and Hawkings equation is applied to simulate the aerodynamic and aeroacoustic characteristics of wings at low-Reynolds number flow. Numerical results demonstrate that the bioinspired wings have excellent aerodynamic performances and remarkable lower overall sound pressure level compared to NACA 0016 which has similar relative thickness. In addition, the unsmooth structure of leading edge waves and trailing edge serrations provide an additional 4.27 dB noise suppression effect, with little impact on aerodynamic characteristics at small angle of attack. The detailed analysis reveals that, due to the special owl-based profile, the flow around two bioinspired wings is mainly turbulent on the upper and lower surfaces, and no laminar separation bubble is detected at the trailing edge. Moreover, the unsmooth structure modifications successfully weaken the scale and scope of coherent vortex structures. These factors contribute to reducing the associated pressure fluctuation, thereby controlling the aeroacoustic noise of wing. Consequently, a coupled bionic wing is presented with the excellent aerodynamic and aeroacoustic characteristics. The conclusions are envisioned to be beneficial to the design of new generation low-noise aeronautical machinery.